Physiological quality of soybean seeds produced under shading (Revista de Ciências Agroveterinárias, 2023)
Low light intensity reduces the production of photoassimilates by plants and consequently the accumulation of reserves in seeds. The objective was to evaluate the physiological quality of soybean seeds produced under shading initiated at different crop phenological stages. In a completely randomized design, the experiment was carried out in a greenhouse, at CAV/UDESC, during the 2018/2019 harvest, with nine treatments and 10 replications. The treatments consisted of nine seed lots, eight of which were obtained from plants submitted to continuous 70% shading, initiated at different phenological stages: stage V6 (Day Julian 07); R1 (JD 14); R2 (JD 21); R3 (JD 28); R4 (JD 35); R5 (JD 42); start of R6 (JD 49); end of R6 (JD 56), and a lot of seeds produced without shading (control). Each repetition consisted of a pot containing a soybean plant. The germination potential and vigor of the seeds produced were evaluated. Soybean seed germination was higher in the lot of seeds from shaded plants from the R4 stage (JD 35), with 98%, but the other lots presented percentages above 87%. The vigor in the accelerated aging test was lower for the lot obtained from shaded plants from V6, with 43%. The dry mass of seedlings showed a 7.0 to 13.3% reduction in relation to the control when the shading was imposed between R3 and R6. It was concluded that the continuous 70% shading in soybeans promoted higher seed germination when imposed from the R4 stage; however, the vigor was dependent on the stage that the shading started and the test used.
Keywords: photosynthesis; germination; Glicyne max; solar radiation; soybeans; seeds